2018
DOI: 10.1007/s00192-018-3721-4
|View full text |Cite
|
Sign up to set email alerts
|

What is the ideal antibiotic prophylaxis for intravesically administered Botox injection? A comparison of two different regimens

Abstract: We found a significantly lower rate of UTIs when patients received a 3-day course of a fluoroquinolone orally as opposed to a single dose of a third-generation cephalosporin IM. Patients with a positive preprocedure culture might benefit from an even longer duration of antibiotics at the time of Botox® injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It is important to emphasize that the length of time used to define our postprocedure UTIs affects our incidence of UTI compared with previous studies. The overall incidence of UTI in our population was 12.9%, on the lower end of the range of results from prior [22][23][24][25] Thirty days postprocedure likely better reflects the results of prophylactic antibiotics given during or immediately after the procedure, as they are unlikely to influence UTI rates as far out as 90 days after the procedure. Urinary retention is often thought to increase the rate of UTI after intradetrusor onabotulinumtoxinA injections.…”
Section: Discussionmentioning
confidence: 79%
“…It is important to emphasize that the length of time used to define our postprocedure UTIs affects our incidence of UTI compared with previous studies. The overall incidence of UTI in our population was 12.9%, on the lower end of the range of results from prior [22][23][24][25] Thirty days postprocedure likely better reflects the results of prophylactic antibiotics given during or immediately after the procedure, as they are unlikely to influence UTI rates as far out as 90 days after the procedure. Urinary retention is often thought to increase the rate of UTI after intradetrusor onabotulinumtoxinA injections.…”
Section: Discussionmentioning
confidence: 79%
“…A recent review on duration of prophylaxis noted a significant decrease in infection with three days of a fluoroquinolone compared to a single dose of ceftriaxone (20.8% vs 36%, p = 0.04). 16 Another study found no difference in infection when comparing antimicrobial type or route of administration. 14 Further study is required to champion antimicrobial stewardship and identify the optimal regimen and duration of prophylaxis for intravesical BoNT.…”
Section: Discussionmentioning
confidence: 99%
“…During the first 12 months after BoNT treatment, up to 35% of patients have UTIs, even when treated with perioperative antibiotics [ 7 ]. When comparing perioperative regiments, a three-day regimen of oral fluorchinolone was superior to a single dose of intramuscular ceftriaxone [ 25 ]. A treatment with ciprofloxacin started prior to injection decreased the risk of UTI when compared to a treatment started after injection [ 26 ].…”
Section: Discussionmentioning
confidence: 99%